New Ag8PtO6: Synthesis, crystal structure, physical properties and theoretical analyses - Thakur, Gohil Singh; Reuter, Hans; Rosner, Helge; Fecher, Gerhard H.; Felser, Claudia; Jansen, Martin (Dalton Transactions, 2019)
We report the synthesis, crystal structure, and basic physical properties of Ag 8 PtO 6 , which represents the first silver platinum ternary oxide. The crystalline compound was obtained from appropriate mixtures of the binary constituents under alkaline conditions at high oxygen pressure, while applying relatively mild thermal conditions (573 K). Ag 8 PtO 6 crystallizes in a new crystal structure in the triclinic system (P1). The structure consists of slightly distorted, discrete PtO 6 octahedra, which are linked via O-Ag-O dumbbells to form a three dimensional framework. It is a diamagnetic semiconductor with a band gap of 0.9 eV. DFT based calculations confirm an electronic ground state that corresponds to a 5d 6 6s 0 configuration of the Pt atoms, in accordance with the observed diamagnetism.
CRIS-Team Scopus Importer:2022-04-14